The Influence of Leadership Styles on Micro and Small Enterprises’ Performance: The Case of Worabie Town, Siltie Zone - Hayru Lale (MBA); Habtamu Kebede (MA) (International Journal of Engineering and Management Research, 2022)
The main objective of the study was to examine the influence of leadership styles on the performance of MSEs in Worabie town. The focus was on three major leadership styles (Autocratic, Democratic and Laissez-faire). The research design was descriptive and analytical type; the research employed both quantitative and qualitative data, which is a mixed approach. Out of 306 total populations, 173 respondents were selected using simple random sampling for questionnaire. The primary data was collected through unstructured interviews and structured questionnaire. The data was analyzed using the descriptive statistics and the regression technique. The results of descriptive statistics showed that the practiced leadership style at the Worabie town by MSEs is mainly autocratic leadership. The result of the regression analysis indicated that democratic leadership style showed a positive and significant influence on MSEs’ performance since beta coefficient value of this style is 0.371 with significant value of (p=0.000), whereas the autocratic and laissez-fair leadership styles showed a significant and negative influence on MSEs’ performance since coefficient value of these styles are -0.306,-0.143 with significant value of (p=0.000 and 0.045) respectively. Concerning socio-demographic variables, beta coefficient of education is = 0.323 with significant value (p= 0.000).Which shows high positive and significant influence on MSEs’ performance; age indicated negative influence on MSEs’ performance while beta coefficient value of gender is 0.126, with (p= 0.108), which indicated that gender difference didn’t show a significant effect on performance of MSEs. The research recommended that, MSE leader’s need to encourage employee participation and involvement in decision making and problem solving in order to develop employees sense of ownership and belongingness through democratic leadership.